92. Jimokɨ irua: Juúragai - Zafiama, Elicio (Universidad Nacional de Colombia, sede Amazonia, 2019)
Canto de la variante jimokɨ ejecutado por Elicio Zafiama, con el grupo de cantores sentado en Nokaido. Este canto hace parte de la colección de cantos del ritual yuakɨ murui-muina (ritual de frutas) del pueblo murui, colección que fue hecha por el Grupo de Danza Kaɨ Komuiya Uai con apoyo de la UNAL, sede Amazonia.

Song from the jimokɨ variant performed by Elicio Zafiama, with the group of singers seated in Nokaido. This song is part of the collection of songs from the yuakɨ murui-muina ritual (fruit ritual) of the Murui people, a collection that was compiled by the Kaɨ Komuiya Uai Dance Group with support from UNAL, Amazonia campus.
Canto de la variante jimokɨ
Keywords: Jimokɨ; Yuakɨ; Baile de frutas; Murui; Ritual chants